Pelatihan Pengembangan Biskuit Yang Diperkaya Tepung Pisang Tongka Langit dan Ikan Cakalang Di Desa Waiheru Kota Ambon - Muhamad Asrar; Ety Yuni Ristanti (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of this community service activity is to increase the knowledge and skills of mothers in making Tongka Langit banana and skipjack flours and processing them into biscuits. The method used in this community service activity consists of the preparation of participants, locations, tools and materials, implementation of activities with the delivery of materials and practices. The results of the activity were 30 mothers attended, there was an increase in participants' knowledge about the nutritional value and benefits of tongka langit bananas, skipjack fish, how to make flour and biscuits enriched with tongka langit bananas and skipjack flours. All participants were able/skilled in making biscuits enriched with banana flour tongka Langit and skipjack tuna.